PHYSIOLOGICAL EFFECTS OF NUTRITIONAL FACTORS ON DENTAL HEALTH - Loredana Liliana Hurjui; Cristina Claudia Tarniceriu; Mihaela Mitrea; Maria Ruxandra Hurjui; Raluca Jipu; Claudia Doruș; Carina Balcoș; Adina Armencia; Ancuța Goriuc; Diana Popovici; Ion Andrei Hurjui; Irina Gradinaru (Romanian Dental Association for Education, 2022)
Considering that, unlike bone tissue, teeth do not change their composition to a small extent after they have been definitively formed, special attention regarding the relationship between nutritional factors and dental development must be directed to the children. The primary dentition begins to develop after two months of intrauterine life, and the permanent dentition a few months before birth. Important nutritional deficiencies during pregnancy can induce malformations in the child and susceptibility to dental caries. In turn, children with chronic nutritional imbalances (deficiencies or excesses in some nutrients) may present with late tooth eruptions, compromising the integrity of the teeth and increasing the frequency of caries.